Agarose gel coated glass substrate for formaldehyde sensing application - Jali, Mohd Hafiz; Abdul Rahim, Hazli Rafis; Md Johari, Md Ashadi; Ahmad, Aminah; Baharom, Mohamad Faizal; MALEK FAISAL, NUR NADIRA; Adnan Zain, Huda; Wadi Harun, Sulaiman (Wydawnictwo SIGMA-NOT, 2022)
This paper demonstrated an intensity modulation detection system employing agarose gel coated on the glass substrate for formaldehyde sensing application. The objectives of this work is to develop a simple and low cost formaldehyde sensor using commercially available microscope glass substrate, coating material and data acquisition unit. The glass substrate was coated with agarose gel using low temperature synthesis method which has superiority in term of high porosity and capable to absorb molecule around it. The formaldehyde detection is based on the change in refractive index (RI) of the agarose gel as a coating material. The RI change of the coating materials will modulate the output light intensity when the concentration level of the formaldehyde varies. This is due to the intensity of the light weakening by absorption and scattering when light propagated through the sensing material. A significant response to formaldehyde concentrations was observed with the output voltage reduced linearly from 1.1V to 0.4V. The sensitivity and the linearity of the proposed sensor improve by a factor of 1.02 and 1.03 respectively as compared to uncoated glass substrate. Moreover, it performs better in term of stability, hysteresis and time response. The proposed formaldehyde sensor avoid utilization of costly optical sensor setup based on laser source which are not feasible for large scale production. Based on the experiment results, the proposed sensor has a good potential as a formaldehyde sensor which is essential for food, health and environmental sector.